Why introduce a bonus for ordinary offense in water polo - Lozovina, M.; Lozovina, V. (Sport Science - International Scientific Journal of Kinesiology, 2019)
By analyzing 23 official matches (13 matches of the Regional Triglav Water Polo League League and 10 games of the LEN Euro Cup played in 2018) by registering 9 originally measured variables and 6 derived, we came to the information on the awarded and played slight offenses in the match or quarter of a game. Based on the obtained results, we suggest introducing the "Bonus" in the water polo. The bonus would be calculated for each quarter and the number of minor offenses for which the team time in the "bonus" would be 7. Any subsequent legal offense would be punished by a free shot from 6m. For a committed minor offense after the bonus expires, the offender would have been granted only a minor offense because we consider that a freethrow penalty form 6m is appropriate to the weightiness of the offense.